The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.3390/ijms222112024
|View full text |Cite
|
Sign up to set email alerts
|

An Insight into the Role of Postmortem Immunohistochemistry in the Comprehension of the Inflammatory Pathophysiology of COVID-19 Disease and Vaccine-Related Thrombotic Adverse Events: A Narrative Review

Abstract: On 11 March 2020, the World Health Organization (WHO) declared a pandemic due to the spread of COVID-19 from Wuhan, China, causing high mortality rates all over the world. The related disease, which mainly affects the lungs, is responsible for the onset of Diffuse Alveolar Damage (DAD) and a hypercoagulability state, frequently leading to Severe Acute Respiratory Syndrome (SARS) and multiorgan failure, particularly in old and severe-critically ill patients. In order to find effective therapeutic strategies, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 44 publications
0
7
0
1
Order By: Relevance
“…From these cases of seriously ill COVD-19 patients, it was observed that the pulmonary tissue was infiltrated with immune cells ( 20 ). Initially, lymphocytes and macrophages were reported to be the dominating cell types ( 22 ), but later studies also showed that PMNs were important players ( 23 ). This discrepancy was probably due to that the latter observation were obtained in patients with earlier disease.…”
Section: Thromboinflammatory Changes In Various Tissues Of Covid-19 P...mentioning
confidence: 99%
“…From these cases of seriously ill COVD-19 patients, it was observed that the pulmonary tissue was infiltrated with immune cells ( 20 ). Initially, lymphocytes and macrophages were reported to be the dominating cell types ( 22 ), but later studies also showed that PMNs were important players ( 23 ). This discrepancy was probably due to that the latter observation were obtained in patients with earlier disease.…”
Section: Thromboinflammatory Changes In Various Tissues Of Covid-19 P...mentioning
confidence: 99%
“…8,9 The corresponding histological findings are represented by diffuse alveolar damage in exudative or proliferative stage, inflammatory cell infiltrates, squamous metaplasia, type 2 pneumocyte activation and fibrin microthrombi formation within pulmonary, cardiac, renal and hepatic circulation. [10][11][12][13] Postmortem examinations are the gold standard for understanding the pathophysiological pathways of diseases and the prime objective of the forensic autopsy is to provide answers about the cause of death. 14 In order to predict the prognosis of COVID-19 in a personalized approach, a set of time and cost-efficient biomarker signatures must be selected.…”
Section: Introductionmentioning
confidence: 99%
“…The corresponding histological findings are represented by diffuse alveolar damage in exudative or proliferative stage, inflammatory cell infiltrates, squamous metaplasia, type 2 pneumocyte activation and fibrin microthrombi formation within pulmonary, cardiac, renal and hepatic circulation. 10–13 …”
Section: Introductionmentioning
confidence: 99%
“…The articles included in this Special Issue are focused on prevention, diagnostics, signatures of the disease course, molecules involved, vaccine-related adverse effects, potential treatments, and short- and long-term consequences. There are 3 original research papers [ 2 , 3 , 4 ] and 11 review articles [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
mentioning
confidence: 99%
“…The work by Chiara Stassi and colleagues [ 9 ] explores the significance of postmortem immunohistochemistry in understanding the pathophysiology of both COVID-19 and COVID-19 vaccine-related adverse rare effects. Maria Narożna and Błażej Rubiś [ 10 ], in their article, discuss the necessity of identification of novel strategies and markers as well as diagnostic methods in the fight against the COVID-19 pandemic.…”
mentioning
confidence: 99%